PERAN LEMBAGA ADAT MELAYU KOTA JAMBI DALAM MELESTARIKAN PROSESI PERNIKAHAN DI SEBERANG KOTA JAMBI TAHUN 1950-2020 - Mawaddah, Aulia; Azmi, Ulul; Syaputra ZE, Deki (Universitas Batanghari Jambi, 2023)
Lembaga Adat Melayu Jambi City is an institution that plays an important role in fosteringand maintaining the existence of Jambi Malay customs including keeping marriage customsrunning in accordance with customs. The purpose of this study is tofind out the traditionalJambi Malay wedding procession across Jambi City and the role of the Jambi City MalayCustomary Institute in preserving the wedding procession across Jambi City in 1950-2020.The research use historical method consisting of heuristics, criticism, interpretation, andhistoriography. Data sources are obtained through interviews, archives and other sources inthe form of books and articles. The results showed that there has been a change in the weddingprocession of the people across the city of Jambi where full customs have begun to be rarelyimplemented. To maintain the wedding customs, the Malay Customary Institute of Jambi Citymade efforts in the form of an appeal for the implementation of marriage to use Jambi-nuancedcustoms, this appeal was conveyed to the bride's makeup, warriors, and wedding clothes, thenalso conveyed to the head of the RT as the regent and head of the Customary Institution at eachlevel.